Greater Risk Taking in Cosmetic Surgery Acceptance and History: An Experimental and Computational Study - Jenkinson, Paul Mark (Aesthetic Plast Surg, 2024)
Cosmetic surgery is ever more affordable and accessible, but carries physical and psychological risks. Yet, no study to date has directly examined risk-taking behaviour under controlled conditions, beyond self-report and in relation to cosmetic surgery attitudes. We used the Balloon Analogue Risk Task and advanced computational modelling to measure decision-making behaviour and identify the latent parameters driving behaviour associated with cosmetic surgery attitudes in women with no cosmetic surgery history (N = 265) and a subsample of women with a cosmetic surgery history (N = 24). Risk taking was higher in women with greater acceptance and history of cosmetic surgery. Computational modelling revealed increased risk taking in women with greater acceptance of cosmetic surgery when decisions were made with greater knowledge of loss (risk) and not when the likelihood of loss was unknown (uncertainty). When women with greater acceptance of cosmetic surgery made decisions, they also placed less emphasis on possible losses (reduced loss aversion). Our findings suggest that women seeking cosmetic procedures may be less sensitive to losses and thus make more risky decisions. Greater emphasis should be placed on communicating potential losses rather than just the associated risks to women considering cosmetic procedures. No Level Assigned This journal requires that authors assign a level of evidence to each submission to which Evidence-Based Medicine rankings are applicable. This excludes Review Articles, Book Reviews, and manuscripts that concern Basic Science, Animal Studies, Cadaver Studies, and Experimental Studies. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s00266-024-03910-9.